Womens experience of sexual harassment in carpet factory. - Dhakal, Gita Kumari (2008)
ABSTRACT: The descriptive study entitled," Womens Experience of Sexual Harassment in Carpet Factory" was carried out as a partial fulfillment for the Masters Degree in Nursing. The objective of the study was to find out the sexual harassment that working women go through in their workplace and its impact on them. A total of 101 working women in six carpet factories were selected by using non-probability purposively sampling. The organizational context and job context of the organization of those factories was also studied. A semi-structured questionnaire was used to collect information on experience of sexual harassment and its impact on their job, mental and physical health. The researcher herself had taken personal interview with the managers of six carpet factories as well as working women of those factories. The study findings revealed that 69.30% respondents were at the age group of 20 to 30 years. Among the total area. While associating the respondents, 66.34% were Tamangs and 776.23% could not read and write (illiterate). Only 72.27% respondents had heard about "Sexual Harassment" and among them 52.05% had faced sexual harassment in their working experience of sexual harassment with respondent's age, ethnicity, marital status, educational level and working experiences, it was found that unmarried workers faced more sexual harassment in comparison to the married workers. Passing vulgar jokes, remarks or teasing obscenely were the most frequent type of sexual harassments (86.84%) and 66% respondents told that the perpetrators were their co-workers. Respondents often experienced sexual harassment while they were working. In the response to harassment, they often ignored the incidence or carried out verbal or physical assault to the harasser by themselves. Study also received that sexual harassment causes negative impact on women physical as well as mental health and their attitude toward the job, as 23% of the women had some disruption on their job. Likewise 61% workers were affected mentally and 7.89% were affected physically after the harassment. Regarding the use of preventive measures of sexual harassment, all the respondents felt need for the provision and execution of penalty to the perpetrator, But none of the carpet factories had policy on sexual harassment. Managers of the carpet factories also expressed the need for a policy in their organization to maintain a fair and productive working environment.